Peningkatan Produktivitas melalui Beban Kerja, Stres Kerja dan Iklim Organisasi pada PT XYZ: Penelitian - Akhmad Nurrofi; Nuruddin Mahmud; Bayu Teguh Wibowo; Antonius Along (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effect of workload, work stres and organizational climate at PT. XYZ on emplyee work produktivity. The sample used in this study was 60 employees of PT. XYZ who work in the sewing operator section. The data collection techmique used was by using a survey in the form of a questionnaire and distributed to employees of PT.XYZ. who work in the sewing operator section. The Data analysis method used in this study is SPSS struktural equation analysis and processed using the SPSS application Version 21. The resultts of the analysis using SPSS show tha. Workload has a positive and significat effect on employee productivity, workloas has a positive and significamt effect on employee work productivity.